Intraparotid Facial Nerve Schwannoma: An Enigma for Surgeons - MHM Anand; Arvind Krishnamurthy; B. Gurukeerthi (Journal of Indian Association of Pediatric Surgeons)
Intraparotid schwannoma is a peripheral nerve sheath tumor arising from the facial nerve. Because of their rarity, surgeons always confront with diagnostic dilemmas. Since it is frequently diagnosed in the younger age group, surgical management is quite challenging. Meticulous dissection of the facial nerve during the surgery is of utmost importance. We report a case of 10-year-old boy with parotid swelling, who underwent superficial parotidectomy in our center. The final histology showed intraparotid schwannomma.